Community Health Scholars: a summer program developing a public health workforce pipeline for diverse high school students - Tagorda-Kama, Michelle; Nelson-Hurwitz, Denise C. (Frontiers in Public Health, 2023)
In response to the growing interest in public health and needs to both increase and diversify the public health workforce, opportunities to engage students early in their educational journey are essential. The University of Hawai‘i at Mānoa launched the Community Health Scholars Program to provide activities for high school students to learn about and build enthusiasm for the field of public health. During the 6-week, in-person summer program, students underrepresented in higher education and who are from historically underrepresented communities completed a college course and participated in activities to enhance their successful entry into a higher education institution. The Community Health Scholars completed an introduction to public health course and gained an array of public health skills through different hands-on activities. The students gained self-confidence and expanded their social capital by attending workshops led by campus faculty, staff, and community partners. A final project highlighting what students learned about themselves and their community was part of a final program showcase. Here we share information about the process of developing the program, the components of the program curriculum, and feedback from both students of the initial cohort and program faculty, where overall satisfaction with the program was reported.